The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/01.bot.0000462956.71988.b6
|View full text |Cite
|
Sign up to set email alerts
|

II–1 Compliance of Low-Intensity Pulsed Ultrasound (LIPUS) for Fresh Fractures

Abstract: Introduction: Some reports showed that low intensity pulsed ultrasound (LIPUS) could stimulate mesenchymal stromal cell (MSC) differentiation into osteo/chondrocyte in vitro. The purpose of this study was to investigate whether LIPUS treatment combined with cell therapy could affect cartilage regeneration in rats which have poor intrinsic repair capacity.Materials and Methods: Eight weeks old male Wistar rats were used in this study. An osteochondral defect, 1mm in diameter, was created on both sides of femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In LIPUS trials with a successful outcome,5–7,1216 wherein the study met the protocol-defined end point, the average compliance was 88% (range: 72%–100%), whereas for trials where the primary end point was not met, the compliance was 54% (range: 43%–95%) 17–20. Moreover, eight out of ten trials with patient compliance higher than 72% reported a successful outcome,5–7,1216 whereas two clinical trials that reported poor patient compliance resulted in unsuccessful outcomes. In the two trials that had high compliance but did not result in a successful outcome,17,18 other factors may have confounded the results.…”
Section: Resultsmentioning
confidence: 99%
“…In LIPUS trials with a successful outcome,5–7,1216 wherein the study met the protocol-defined end point, the average compliance was 88% (range: 72%–100%), whereas for trials where the primary end point was not met, the compliance was 54% (range: 43%–95%) 17–20. Moreover, eight out of ten trials with patient compliance higher than 72% reported a successful outcome,5–7,1216 whereas two clinical trials that reported poor patient compliance resulted in unsuccessful outcomes. In the two trials that had high compliance but did not result in a successful outcome,17,18 other factors may have confounded the results.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, motivation and dedication of the patients plays an indispensable role in the study outcome. Certain factors, such as age and fracture site, could significantly affect the adherence to the prescribed LIPUS protocol (Matsubara et al, 2015). The detailed description of patient compliance in the reviewed studies is summarised in Table 1-3. There is a considerable variability in documentation regarding patients' compliance in LIPUS clinical trials.…”
Section: Lipus and Patient Compliancementioning
confidence: 99%
“…It is not always clear, though, whether the active minutes were counted only when the device was in direct skin contact, as it was described in some studies (Emami et al, 1999;Zacherl et al, 2009). Overall, there is a trend towards positive regenerative outcomes of the LIPUS application in clinical trials with increasing patient device-application compliance (Gopalan et al, 2020;Maurya et al, 2019;Namera et al, 2020;Nolte et al, 2001;Roussignol et al, 2012;Santana-Rodríguez et al, 2019;Schofer et al, 2010;Tsumaki et al, 2004). Studies, where around 30 % of the patients performed less than 50 % of LIPUS applications found LIPUS ineffective (Emami et al, 1999;TRUST Investigators writing group et al, 2016;Simpson et al, 2017).…”
Section: Lipus and Patient Compliancementioning
confidence: 99%
See 1 more Smart Citation